The Relationship Evaluation Process scale: A multidimensional measure of how people assess the quality of their romantic relationships. (November 2019) - Buckingham, Justin T.; Yamkovenko, Bogdan; Boring, Brandon L.; Andrade, Fernanda C.; Iafolla, Cristiana
Improving on previous measures, we developed a multidimensional measure of relationship evaluation processes (REPs). In Study 1 ( N = 523), we used exploratory factor analysis to identify the following eight dimensions: personal standards, social comparison, upward social comparison, past comparison, upward past comparison, feedback, negative behavior, and feared future. In Study 2 ( N = 469), we used a more diverse sample to confirm the factor structure. In both studies, bivariate correlations suggested that people who more frequently engage in REPs tend to have lower relationship satisfaction. Negative behavior and feared future were strong predictors of relationship dissatisfaction in both studies; Study 2 showed that these factors mediate the relationship between neuroticism and satisfaction. The present research moves the literature beyond its focus on personal standards and social comparison to consider the important roles of other REPs.